Effect of Brief Mindfulness Induction on University Athletes’ Sleep Quality Following Night Training - Li, Chunxiao; Kee, Ying Hwa; Lam, Lok Shan (Frontiers in Psychology, 2018)
Given the need to alleviate sleep problems confronting athletes, the present experiment, conducted as much as possible in a naturalistic fashion that mimics daily life, seeks to examine whether a brief mindfulness induction immediately prior to sleep following night training can improve athletes’ sleep. A sample of university athletes (n = 80) was recruited and 63 of them were eligible to participate in this experiment. They were then randomly assigned into experimental group (n = 32) and control group (n = 31). Following night training and just prior to sleep, those in the experimental group received a self-administered brief 6-minute mindfulness induction via a video clip, whereas the control group participants viewed a similar 6-minute video devoid of mindfulness induction passively. Questionnaire-based measures of training intensity, pre-sleep arousal, state mindfulness, and sleep diary (i.e., level of rest, sleep duration, and overall sleep quality) were administered. Results showed that brief mindfulness induction reduced pre-sleep arousal, and improved level of rest and overall sleep quality, but not sleep duration. Pre-sleep arousal was also found to be a partial mediator in the relationship between the brief mindfulness induction and reported level of rest during sleep. These findings suggest the brief mindfulness induction may be an effective approach for decreasing pre-sleep arousal and improving sleep quality after night training among athletes.